2022
DOI: 10.3390/microorganisms10051040
|View full text |Cite
|
Sign up to set email alerts
|

The Notable Achievements and the Prospects of Bacterial Pathogen Genomics

Abstract: Throughout the entirety of human history, bacterial pathogens have played an important role and even shaped the fate of civilizations. The application of genomics within the last 27 years has radically changed the way we understand the biology and evolution of these pathogens. In this review, we discuss how the short- (Illumina) and long-read (PacBio, Oxford Nanopore) sequencing technologies have shaped the discipline of bacterial pathogen genomics, in terms of fundamental research (i.e., evolution of pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 115 publications
0
8
0
Order By: Relevance
“…Comparing the results between SRS and LRS, different studies highlight genome regions where the SRS lacks accuracy due to limit of the technology ( Modlin et al, 2021 ; Peker et al, 2021 ; Gómez-González et al, 2022 ; Marin et al, 2022 ). Although LRS approaches still present a high-error rate (~5–15%), their random nature allows to improve accuracy with higher coverage ( Rhoads and Au, 2015 ; Athanasopoulou et al, 2021 ; Amoutzias et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the results between SRS and LRS, different studies highlight genome regions where the SRS lacks accuracy due to limit of the technology ( Modlin et al, 2021 ; Peker et al, 2021 ; Gómez-González et al, 2022 ; Marin et al, 2022 ). Although LRS approaches still present a high-error rate (~5–15%), their random nature allows to improve accuracy with higher coverage ( Rhoads and Au, 2015 ; Athanasopoulou et al, 2021 ; Amoutzias et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rapid tests for the detection of the main resistance enzymes in Gram-negative bacteria have been developed with the final objectives of implementing efficient infection control measures and identifying resistance mechanisms so that the most appropriate antibiotic treatment can be started. E. coli belongs to the small number of Gram-negative bacteria with significant clinical impact and is, therefore, one of the most studied [ 24 ]. This study reported a real-life experience assessing the impact on clinicians’ confidence and antimicrobial prescription of a newly introduced diagnosis of direct detection of CTX-M ESBL-producers in E. coli -positive BCs in a hospital in which carbapenem-sparing strategies were implemented during the last years, mainly as educational interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Whole-genome sequencing was carried out utilizing long-read Nanopore sequencing, a relatively portable instrument that generates reads with a maximum length and is capable of presenting sequences in real time, to confirm the isolate's correct identification [75] , [76] , [77] , [78] . Long-read Nanopore sequencing was chosen over other short-read high-throughput sequencing methods because they offer insufficient phylogenetic resolution and have a low level of integrity for the majority of the assembled area [79] .…”
Section: Discussionmentioning
confidence: 99%